Hospital emergency department visits made by developmentally disabled adolescents with oral complications - Atchison, Kathryn A.; Bhoopathi, Vinodh; Wells, Christine R. (Frontiers in Oral Health, 2022)
Purpose We used Andersen's Behavioral Model in a cross-sectional study to determine the factors associated with utilization of the emergency department (ED), controlling for whether an adolescent has a developmental disability (DD) and one or more oral complications (toothaches, decayed teeth, bleeding gums, eating or swallowing problems). Methods Data from the 2016–2019 National Survey of Children's Health (NSCH) was used for this secondary data analysis study. We used frequencies and percentages to describe the sample characteristics. Chi-square tests were used for bivariate analyses. Multivariable logistic regression modeling was conducted to predict ED visits by adolescents aged 10–17 controlling for predisposing, enabling, and need variables. Results The sample consisted of 68,942 adolescents who were primarily male, non-Hispanic White, and born in the U.S. Parents reported that 69% of the adolescents had neither a DD nor an oral complication; 10% had no DD but experienced one or more oral complication; 16% had a DD but no oral complication; and 5% had both DDs and one or more oral complication. Adolescents with both a DD and an oral complication reported the highest level of ED visits at 33%, compared to 14% of adolescents with neither DD nor oral complication. Regression analysis showed that adolescents with a DD and oral complication (OR: 2.0, 95% CI: 1.64–2.54, p < 0.0001), and those with DDs but no oral complications (OR: 1.45, 95% CI: 1.25–1.68, p < 0.0001) were at higher odds of having an ED visit compared to those with neither a DD nor an oral complication. Not having a Medical Home increased the likelihood of ED visits by 14% (p = 0.02). Those with private insurance (OR: 0.63, 95% CI: 0.53–0.75, p < 0.0001) and those from a family where the highest level of education was some college and above (OR: 0.85, 95% CI: 0.73–0.98, p = 0.03) were less likely than their counterparts to have had an ED visit. Conclusion Adolescents with DDs and oral complications utilize ED visits more frequently than those with neither DDs nor oral complications. Integrating the dental and medical health systems and incorporating concepts of a Patient-Centered Medical Home could improve overall health care and reduce ED visits for adolescents.